Patient Race and Racial Composition of Delivery Unit Associated With Disparities in Severe Maternal Morbidity: A Multistate Analysis 2007–2014. Issue 3 (24th September 2022) - Sastow, D.L.; Jiang, S.Y.; Tangel, V.E.; Matthews, K.C.; Abramovitz, S.E.; Oxford-Horrey, C.M.; White, R.S.
Abstract : ( Int J Obstet Anesth . 2021;47:103160) Black women have a higher rate of severe maternal morbidity (SMM) than non-Hispanic White women. Although investigations of SMM and race/ethnicity have typically centered around inequalities at the patient level, SMM is also associated with quality of care at the hospital level. Mothers who give birth in hospitals that serve a disproportionate number of black women (Black-serving hospitals) are more likely to have SMM than mothers who deliver at hospitals that serve fewer black women. Likewise, mothers who deliver at hospitals with a relatively greater proportion of patients without insurance or on public insurance (safety-net burden) have an increased risk for SMM. Few studies have investigated the relationship between hospital-level and patient‐level factors and risk for SMM. Using State Inpatient Databases (SID), data from Healthcare and Cost and Utilization Project (HCUP), and Agency for Healthcare Research and Quality (AHRQ) for the years 2007–2014, this retrospective observational study attempted to calculate the odds of SMM with the hospital-level factors of safety-net burden and Black-serving classification, both separately and in conjunction with the patient's race/ethnicity.